2018
DOI: 10.7324/ijcrr.2018.1041
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health - An Effective Nutrition Communication Tool

Abstract: Information, education and communication approaches were used in this study to reach the target groups. Nutrition education was provided in the form of text messages integrated with mobile communication, an alternative choice of media already popular among college going girls instead of usual nutrition education practices. 284 college going girls were divided into cases and controls, with proportion of 1:1 ratio, from various institutions with English medium of instruction and using mobile phones were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This finding demonstrates a risk consideration in undergraduate nutrition education at the University of Jordan's School of Educational Sciences, highlighting the urgent need to improve their nutrition knowledge, which plays a crucial role in their dietary intake choices and healthy food consumption [77][78][79][80][81][82]. In addition, further research [42,[47][48] has proved the benefit of mHealth applications in boosting nutrition awareness among their users. Therefore, this lack of nutrition awareness among undergraduates might be remedied by employing various tactics, such as providing online nutrition intervention programs or encouraging students to utilize nutrition-related mobile applications to increase their understanding.…”
Section: The Intensity Use Of Mhealth Applications Nutrition Knowledg...mentioning
confidence: 82%
See 1 more Smart Citation
“…This finding demonstrates a risk consideration in undergraduate nutrition education at the University of Jordan's School of Educational Sciences, highlighting the urgent need to improve their nutrition knowledge, which plays a crucial role in their dietary intake choices and healthy food consumption [77][78][79][80][81][82]. In addition, further research [42,[47][48] has proved the benefit of mHealth applications in boosting nutrition awareness among their users. Therefore, this lack of nutrition awareness among undergraduates might be remedied by employing various tactics, such as providing online nutrition intervention programs or encouraging students to utilize nutrition-related mobile applications to increase their understanding.…”
Section: The Intensity Use Of Mhealth Applications Nutrition Knowledg...mentioning
confidence: 82%
“…In addition, previous research on nutrition knowledge has demonstrated a correlation between the use of mHealth applications and an increase in nutrition knowledge [42]. It is equally effective as a nutrition communication tool: enhancing nutritional knowledge through the transmission of nutrition messages improves eating perception, nutrition knowledge, motivation, and healthy eating behaviors [47][48].…”
Section: Mhealth Apps and Nutrition Knowledgementioning
confidence: 99%